THE INFLUENCE OF LOCAL OWN-SOURCE REVENUE AND EQUALIZATION FUNDS ON ECONOMIC GROWTH IN THE PROVINCE OF SUMATERA UTARA - Sinta, Sinta; Asnawi, Asnawi; Roni, Muhammad (Journal of Malikussaleh Public Economics, 2024)
The study sought to ascertain the effects of the General Allocation Fund, Special Allocation Fund, and Local Revenue on North Sumatra Province's economic expansion. The review utilized Time Series information from 1990-2023. The review utilized the Autoregressive Circulated Slack (ARDL) strategy. Short-term research reveals that the variables Local Revenue and General Allocation Fund have a negative and insignificant effect on North Sumatra Province's economic growth, while the variable Special Allocation Fund has a positive and insignificant effect. In the long haul, Nearby Income significantly affects Financial Development in North Sumatra Area. The North Sumatra Province's economic growth is not significantly impacted by the General Allocation Fund. The North Sumatra Province's economic growth is boosted significantly by the Special Allocation Fund.